School mini-garden as tools for environmental education at the Santo Antônio municipal school, Grajaú, State of Maranhão (MA), Brazil (Research, Society and Development, 2024)
Environmental Education plays an important role in the interaction between society and nature. Thus, the object of study of this work was the implementation of a mini-garden at Escola Municipal Santo Antônio, Grajaú-MA. The objective of the research was to investigate the potential of the mini-garden as an educational tool to promote environmental education, encouraging students to grow and consume healthy food. The research's methodological approaches were qualitative research and action research, using participant observation, the application of closed questionnaires and the practice of didactic sequences as ways of obtaining data. The results indicate that students at the researched school recognize the importance of preserving nature and the environment, demonstrating the effectiveness of the mini-garden as an educational tool in promoting environmental and interdisciplinary education, in which students can explore scientific and empirical concepts, and, add issues related to healthy eating. The Environmental Education approach based on the interaction of theory and practice stimulates students' interest and makes learning more meaningful. In this context, the students surveyed were motivated and willing to participate in activities related to the implementation of the mini-garden. Therefore, this study highlights the relevance of Environmental Education in the training of individuals, highlighting the importance of the school mini-garden as an instrument for teaching and learning and for socio-environmental awareness.